Collision cross‐section analysis of self‐assembled metallomacrocycle isomers and isobars via ion mobility mass spectrometry. (8th February 2020) - Endres, Kevin J.; Barthelmes, Kevin; Winter, Andreas; Antolovich, Robert; Schubert, Ulrich S.; Wesdemiotis, Chrys
Abstract : Rationale: Coordinatively driven self‐assembly of transition metal ions and bidentate ligands gives rise to organometallic complexes that usually contain superimposed isobars, isomers, and conformers. In this study, the double dispersion ability of ion mobility mass spectrometry (IM‐MS) was used to provide a comprehensive structural characterization of the self‐assembled supramolecular complexes by their mass and charge, revealed by the MS event, and their shape and collision cross‐section (Ω), revealed by the IM event. Methods: Self‐assembled complexes were synthesized by reacting a bis(terpyridine) ligand exhibiting a 60 o dihedral angle between the two ligating terpyridine sites (T ) with divalent Zn, Ni, Cd, or Fe. The products were isolated as (Metal 2+ [T ]) n (PF6 )2 n salts and analyzed using IM‐MS after electrospray ionization (ESI) which produced several charge states from each n ‐mer, depending on the number of PF6 ˉ anions lost upon ESI. Experimental Ω data, derived using IM‐MS, and computational Ω predictions were used to elucidate the size and architecture of the complexes. Results: Only macrocyclic dimers, trimers, and tetramers were observed with Cd 2+, whereas Zn 2+ formed the same plus hexameric complexes. These two metals led to the simplest product distributions and no linear isomers. In sharp contrast, Ni 2+ and Fe 2+ formed all possible ring sizes from dimer to hexamer as well as various linear isomers. The experimental and theoretical Ω data indicated rather planar macrocyclic geometries for the dimers and trimers, twisted 3D architectures for the larger rings, and substantially larger sizes with spiral conformation for the linear congeners. Adding PF6 ˉ to the same complex was found to mainly cause size contraction due to new stabilizing anion–cation interactions. Conclusions: Complete structural identification could be accomplished using ESI‐IM‐MS. Our results affirm that self‐assembly with Cd 2+ and Zn 2+ proceeds through reversible equilibria that generate the thermodynamically most stable structures, encompassing exclusively macrocyclic architectures that readily accommodate the 60 o ligand used. In contrast, complexation with Ni 2+ and Fe 2+, which form stronger coordinative bonds, proceeds through kinetic control, leading to more complex mixtures and kinetically trapped less stable architectures, such as macrocyclic pentamers and linear isomers.